(3GdCQTja GdQbej GdEdcJQhfjs (3GdBf hdjS ZOGs - (3UHMj, MGRe MSfs ((3GdLjRI, eUQs (3GdecJHI GdCcGOjejIs, 2007)
(3jJfGhd GdCQTja h eQGcR GdeYdheGJs
hurg
5 11 13
Keywords: (3GdCQTjas; (3GdeYdheGJ, Ydes; (3GdecJHGJ, Ydes; (3eQGcR GdeYdheGJs